PENGAMALAN NILAI-NILAI AKHLAK DAN PENGARUHNYA PADA REMAJA MESJID THAWALIB JALAN SM. RAJA KECAMATAN MEDAN KOTA - Zhukozan Razasqi (Fakultas Agama Islam, 2021)
This study aims to find out what forms of practice of moral values are in the Thawalib Mosque Youth, Sisingamangaraja Street, Medan City District, the practice of moral values for the Thawalib Mosque Youth at Sisingamangaraja Street, Medan City District, and the form of the practice of moral values affects the practice of values. The morality of the youth of the Thawalib Mosque, Sisingamangaraja Street, Medan City District. The population in this study are all teenagers who are members of the Thawalib Mosque Youth organization whose activities are centered at the Thawalib Mosque Jalan SM. The king of Medan Kota sub-district was 46 people. The sample in this study used the entire population (total sampling) as many as 46 mosque youths. The research data was collected through a questionnaire and analyzed using descriptive and correlational analysis techniques using the r Product Moment Correlation formula. Based on the results of data analysis, it was found that: 1) The form of the practice of moral values in the youth of the Thawalib Mosque is to open recitations three times a week whose implementation is centered at the Thawalib Mosque by inviting the Ustad/Ustadzah to give lectures/tausiah. The form of moral practice values is classified into the good category with an average value of 3.20. The forms of practicing these moral values are: Patience and resistance to disturbances, namely refraining from what is hated with pleasure and willingness, putting your trust in Allah SWT in all things, namely doing and hoping with a calm heart. Loving and doing good, Loving and loving yourself, family, other people and creatures. Likes and manifests the truth, which is true in speech, daily interactions, ideals or desires, in promises and in appearance. Tawadhu, namely being humble, not arrogant and not feeling the greatest. Sincere. Diligent, neat, active, polite and istiqamah.